2022
DOI: 10.3389/fpsyg.2021.769459
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Gender Self-Stereotyping and Life Satisfaction: The Mediation Role of Relational Self-Esteem and Personal Self-Esteem

Abstract: Individuals voluntarily internalize gender stereotypes and present personality characteristics and behaviors that conform to gender role requirements. The aim of the current study was to explore the reasons people internalize gender stereotypes. We conducted surveys with 317 college students in China to examine the relationship between gender self-stereotyping and life satisfaction. We also analyzed the mediating roles of relational self-esteem (RSE) and personal self-esteem (PSE) and the moderation role of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…This finding of gender differences is inconsistent with the studies of Park et al ( 61 ), who observed significant changes in the longitudinal relationship between SA and depression among Korean adolescents across time, but no gender differences were found in the strength of these relationships. Possible mechanisms lie in physiological differences between the sexes (e.g., genetic vulnerability) ( 62 ), differences in self-concept ( 63 ), and differences in stress perception ( 64 ) that result in different emotional responses and behavioral patterns. Compared to males, females are more likely to perceive stress, and self-distraction may be considered one of the effective coping mechanisms ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding of gender differences is inconsistent with the studies of Park et al ( 61 ), who observed significant changes in the longitudinal relationship between SA and depression among Korean adolescents across time, but no gender differences were found in the strength of these relationships. Possible mechanisms lie in physiological differences between the sexes (e.g., genetic vulnerability) ( 62 ), differences in self-concept ( 63 ), and differences in stress perception ( 64 ) that result in different emotional responses and behavioral patterns. Compared to males, females are more likely to perceive stress, and self-distraction may be considered one of the effective coping mechanisms ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…The researcher's intention was not to blame or target young mothers and women of Pakistan and their upbringing. In this research, the men's perspective perceived the gendered socialization process (Li, Liu, & Song 2022). Gender stereotyping is a significant factor that reinforces parenting behaviors, making things more complicated while rearing the child.…”
Section: Discussionmentioning
confidence: 94%
“…Research investigating the complex relationship between gender and self-perception within the realm of medical psychology has garnered considerable attention [15,16]. Existing literature underscores the interplay between gender identity and the construction of self-concept, revealing potential disparities in the subjective experiences of individuals based on their gender [17].…”
Section: Discussionmentioning
confidence: 99%